Robotic Process Automation in Healthcare - Streamlining Precision Medicine Workflows With AI (Journal of Science & Technology, 2020)
Robotic Process Automation (RPA) and Artificial Intelligence (AI) are revolutionizing healthcare by enhancing precision medicine workflows. This paper explores how RPA, coupled with AI, streamlines these workflows, improving patient care and treatment outcomes. By automating repetitive tasks, RPA reduces human errors and increases operational efficiency. AI, on the other hand, enhances decision-making by analyzing complex data sets and providing valuable insights. Together, they optimize processes in precision medicine, enabling healthcare providers to deliver personalized and timely care.